Political marketing theory and concepts - Ormrod, Robert; Henneberg, Stephan C. M.; O'Shaughnessy, Nicholas J. 1954- (Los Angeles, California SAGE, 2013)
"Political Marketing: Theories and Concepts provides students with a valuable and critical understanding of how political parties use marketing to attain their aims. Unlike other textbooks, this text explicitly focuses on the theoretical underpinnings and cutting edge concepts used by political parties, allowing students to gain key insights into how they win elections and remain in power. With an engaging and thought provoking topic selection, these field-leading authors have ensured that this often complex and theoretically advanced topic is clearly accessible for a student audience and novice researchers. Key features of each chapter include: Short chapter introduction and learning summaries ; Discussion questions to share in the classroom ; Annotated suggestions for further reading ; Lists of key terms to consider."--Publisher's website.
Introduction -- Theorical Issues in Political Marketing. Defining Political Marketing ; Theories and Concepts in Political Marketing ; The Triadic Interaction Model of Political Exchange ; Critical Perspectives on Political Marketing ; Political Marketing and Theories of Democracy ; The Ethics of Political Marketing. -- Conceptual Issues in Political Marketing. Political Relationship Marketing ; Strategic Political Postures ; Political Market Orientation ; Political Marketing Strategy and Party Organizational Structure ; Symbolism in Political Marketing ; Conclusion: Research Agendas for Political Marketing and Political Marketing Management.
Keywords: Campaign management; Marketing